The roles of employment status and income in the mental health of informal caregivers in Germany - Julia-Sophia Scheuermann; Anna Pendergrass; Katharina Diehl; Raphael M. Herr (BMC, 2024)
Abstract Background Informal caregivers often experience multiple negative consequences as a result of the informal care they provide. Among other factors, employment status, financial resources, and mental health are related to informal caregiving. This analysis examined the association between informal caregivers' employment status and their mental health, as well as the moderating effect of net household income on this relationship. Methods The research question was addressed with data from the German Socio-Economic Panel (SOEP) survey, comprising 3,053 informal caregivers (1,007 male; 2,046 female). Data were obtained through self-reports, and mental health was measured with the Summary Scale Mental Score. Stepwise adjusted multiple linear regression models were used to examine the association between employment status and mental health. The moderating effects were tested with interaction terms. All analyses were also stratified for gender. Results Informal caregivers with full-time jobs reported better mental health than unemployed or marginally employed caregivers (β = 0.077, p < 0.001). The significant interaction term for full-time (β=-0.066, p = 0.001) and part-time workers (β=-0.066, p = 0.003) indicated a moderating effect of net household income on the association between employment status and mental health. This finding was especially evident in women. Conclusions Employment appears to be a relevant protective factor for informal caregivers' mental health. However, if informal caregivers are not employed, a low net household income might additionally restrict their mental health. Therefore, welfare policy structures must be created to reduce the negative financial consequences for informal caregivers and enable them to achieve work-life-care balance.